Psychological Security Among University Students: Highlighting Pre-Service Teachers of Children with Disabilities and Pre-School Children - Al-Zboon, Eman; Jumia'an, Ibrahim (Richtmann Publishing, 2020)
A survey of psychological security among pre-service teachers is significant for policy-makers in health and education services sectors to certify skilled teachers to work with children. So, the purpose of the current study was to investigate the level of psychological security of Jordanian pre-service special education and early childhood teachers. A descriptive method design was adopted. A survey was used to collect data about the level of psychological security of Jordanian pre-service teachers. Participants of the study were 216 special education and early childhood teachers. Results showed that teachers cited average levels of PS and 10.6 % of all participants had a low level of PS. Teachers rated thinking about the future, life being interesting, love between people, and unknown things as problematic issues in PS. Results revealed no statistically significant mean differences due to gender, average achievement or religious commitment. Recommendations for field and future research are presented.